(untitled) (Bangladesh Journal of Botany, 2018)
The diffusion ability and rheological properties of MS medium for germination and growth of tobacco seedlings of cv. Samsun Canik at different pH and concentrations of tragacanth gum were compared. The results showed that 11 g/l tragacanth gum with low osmotic pressure at pH 5.6 - 5.8 offered the best conditions for morphological developments like longer shoots, roots and broader leaves of the seedlings compared to the similar morphological developments on agar solidified MS medium with high osmotic pressure. No aberration was noted in nu1mber of chromosomes of germinated tobacco seedlings on either agar or tragacanth containing medium. On the basis of present findings, it is possible to suggest that tragacanth gum had high potential to replace agar in seed germination studies.